CEACAM1 Activation by CbpF-Expressing E. coli - Shhadeh, Amjad; Galaski, Johanna; Alon-Maimon, Tamar; Fahoum, Jamal; Wiener, Reuven; Slade, Daniel J.; Mandelboim, Ofer; Bachrach, Gilad (Frontiers in Cellular and Infection Microbiology, 2021)
Recent studies on the oral, anaerobic, gram-negative bacterium Fusobacterium nucleatum revealed its presence and involvement in colorectal, esophageal and breast cancer. We previously demonstrated that F. nucleatum binds and activates the human inhibitory receptors TIGIT and CEACAM1 leading to inhibition of T and NK cell anti-tumor immunity. CEACAM1 was found to be bound and activated by the fusobacterial trimeric autotransporter adhesin CbpF. Here we report the generation of a recombinant E. coli expressing full-length CbpF that efficiently binds and activates CEACAM1.